2017
DOI: 10.1161/jaha.117.006579
|View full text |Cite
|
Sign up to set email alerts
|

Sympathomimetic Effects of Acute E‐Cigarette Use: Role of Nicotine and Non‐Nicotine Constituents

Abstract: BackgroundChronic electronic (e) cigarette users have increased resting cardiac sympathetic nerve activity and increased susceptibility to oxidative stress. The purpose of the present study is to determine the role of nicotine versus non‐nicotine constituents in e‐cigarette emissions in causing these pathologies in otherwise healthy humans.Methods and ResultsThirty‐three healthy volunteers who were not current e‐cigarette or tobacco cigarette smokers were studied. On different days, each participant used an e‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 64 publications
6
73
1
7
Order By: Relevance
“…The vertical dashed line represents no effect, and plots to the right of the vertical dashed line indicate that the effect of ECN is greater than that of EC0. The results of most [8,16,34] but not all [2,9] of these acute vaping studies were consistent with the notion that nicotine-and not the non-nicotine constituents-in the EC aerosol was responsible for the acute sympathomimetic effects of EC vaping. The overall mean differences between the ECN and EC0 studies across all studies was 3.73 mmHg (95% CI 0.59-6.87; p = 0.02) for for SBP, 3.25 mmHg (95% CI 1.21-5.30; p = 0.0018) for DBP and 6.44 bpm (95% CI The forest plot of each study represents the mean differences between TCs and ECs, with the corresponding lower and upper 95% confidence bounds.…”
Section: Acute Autonomic Cardiovascular Effects Of Ecn Versus Ec0 Vapingsupporting
confidence: 76%
“…The vertical dashed line represents no effect, and plots to the right of the vertical dashed line indicate that the effect of ECN is greater than that of EC0. The results of most [8,16,34] but not all [2,9] of these acute vaping studies were consistent with the notion that nicotine-and not the non-nicotine constituents-in the EC aerosol was responsible for the acute sympathomimetic effects of EC vaping. The overall mean differences between the ECN and EC0 studies across all studies was 3.73 mmHg (95% CI 0.59-6.87; p = 0.02) for for SBP, 3.25 mmHg (95% CI 1.21-5.30; p = 0.0018) for DBP and 6.44 bpm (95% CI The forest plot of each study represents the mean differences between TCs and ECs, with the corresponding lower and upper 95% confidence bounds.…”
Section: Acute Autonomic Cardiovascular Effects Of Ecn Versus Ec0 Vapingsupporting
confidence: 76%
“…HRV analysis revealed patterns of change indicative of sympathovagal disbalance in the control of the mouse heart due to vaping where LF was increased, HF was decreased and LF/HF ratio increased. These changes are in line with what has been shown in human subjects who use tobacco cigarettes and electronic cigarettes 30 . HF is considered an index of parasympathetic modulation of the heart rate, and LF is considered an index of sympathetic modulation, but the actual contribution of the sympathetic and parasympathetic systems to HRV parameters in normal and abnormal physiology are still being dissected 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, in young healthy nonsmokers, acute inhalation of e-cig vapor increases both systolic and diastolic BP and heart rate (24). In another study, increased heart rate variability was reported following exposure to e-cig with nicotine, but not to e-cig without nicotine, indicating a shift in cardiac sympatho-vagal balance toward sympathetic predominance (101). In young, normotensive nonsmokers, Fogt et al (48) found that e-cig inhalation preferentially increased both resting and exercise diastolic BP 40 min following nicotine inhalation.…”
Section: Nicotine and The Ras In Cardiovascular Dysfunctionmentioning
confidence: 93%